Efficacy and Safety of Modified Banxia Xiexin Decoction (Pinellia Decoction for Draining the Heart) for Gastroesophageal Reflux Disease in Adults: A Systematic Review and Meta-Analysis. (19th February 2017) - Dai, Yunkai; Zhang, Yunzhan; Li, Danyan; Ye, Jintong; Chen, Weijing; Hu, Ling
Abstract : Modified Banxia Xiexin decoction (MBXD) is a classical Chinese herbal formula in treating gastroesophageal reflux disease (GERD) for long time, but the efficacy of it is still controversial. This study is to evaluate the efficacy and safety of MBXD for the treatment of GERD in adults. The search strategy was carried out for publications in seven electronic databases. RevMan software version 5.3 and the Cochrane Collaboration's risk of bias tool were performed for this review. Twelve RCTs were included for the analysis. The results of overall clinical efficacy and efficacy under gastroscope demonstrated that MBXD was superior to conventional western medicine. Meanwhile, the results of subgroup analysis showed clinical heterogeneity between the two groups. However, there was no statistically significant difference in acid regurgitation between the two groups. But in the improvement of heartburn and sternalgia, the results showed statistically significant differences for the comparison between two groups. In addition, the adverse reactions of the experiment groups were not different from those of the control groups. This systematic review indicates that MBXD may have potential effects on the treatment of patients with GERD. But because the evidence of methodological quality and sample sizes is weak, further standardized researches are required.